Evaluation of the efficacy of trigger points combined with extracorporeal shock waves in the treatment of plantar fasciitis: heel temperature and plantar pressure - Wang, Bo; Wang, Xiao-Lei; Ma, Yan-Tao; Wu, Wei; Zheng, Yong-Jun (BMC musculoskeletal disorders, 2024)
Background Plantar fasciitis (PF) is the most common cause of heel pain. Among conservative treatments, extracorporeal shock wave therapy (ESWT) is considered effective for refractory PF. Studies have shown that applying ESWT to the trigger points (TrPs) in the triceps surae may play an important role in pain treatment in patients with PF. Therefore, the purpose of this study was to combine the concept of trigger points and ESWT to explore the effect of this combination on plantar temperature and pressure in patients with PF. Methods After applying inclusion and exclusion criteria, 86 patients with PF were recruited from the pain clinic of Huadong Hospital, Fudan University and randomly divided into experimental ( n = 43) and control groups ( n = 43). The experimental group was treated with extracorporeal shock waves to treat the medial heel pain point and the gastrocnemius and soleus TrPs. The control group was only treated with extracorporeal shock waves at the medial heel pain point. The two groups were treated twice with an interval of 1 week. Primary measurements included a numerical rating scale (NRS) score (overall, first step, heel pain during daily activities), and secondary measurements included heel temperature, Roles–Maudsley score (RMS), and plantar pressure. All assessments were performed before treatment (i.e., baseline) and 6 and 12 weeks after treatment. Results During the trial, 3 patients in the experimental group withdrew from the study, 2 due to interruption of the course of treatment by the COVID-19 epidemic and 1 due to personal reasons. In the control group, 3 patients fell and were removed due to swelling of the heel. Therefore, only 80 patients with PF were finally included. After treatment, the two groups showed good results in NRS score (overall, first step, heel pain during daily activities), RMS, and plantar temperature, especially in the experimental group, who showed a significantly better effect than the control group. Conclusion ESWT of the heel combined with the triceps trigger point of the calf can more effectively improve the pain, function and quality of life of refractory PF than ESWT of the heel alone. In addition, ESWT of the heel combined with the triceps trigger point of the calf can effectively reduce the skin temperature of the heel on the symptomatic side, indicating that the heel temperature as measured by infrared thermal imaging may be used as an independent tool to evaluate the therapeutic effect for patients with chronic PF. Although extracorporeal shock waves combined with TrPs treatment can cause changes in the patients’ gait structure, plantar pressure is still difficult to use as an independent tool to evaluate the therapeutic effect for PF. Trial registration Registered in the Chinese Clinical Trial Registry ( www.chictr.org.cn ) on 12/17/2021 with the following code: ChiCTR-INR-2,100,054,439.